First Description of KPC-2-Producing Klebsiella oxytoca Isolated from a Pediatric Patient with Nosocomial Pneumonia in Venezuela - Indira Labrador; María Araque (Case Reports in Infectious Diseases)
During the last decade, carbapenem resistance has emerged among clinical isolates of the Enterobacteriaceae family. This has been increasingly attributed to the production of β-lactamases capable of hydrolyzing carbapenems. Among these enzymes, Klebsiella pneumoniae carbapenemases (KPCs) are the most frequently and clinically significant class-A carbapenemases. In this report, we describe the first nosocomial KPC-2-producing K. oxytoca isolated from a pediatric patient with pneumonia admitted to the intensive care unit at The Andes University Hospital, Mérida, Venezuela. This strain was resistant to several antibiotics including imipenem, ertapenem, and meropenem but remained susceptible to ciprofloxacin, colistin, and tigecycline. Conjugation assays demonstrated the transferability of all resistance determinants, except aminoglycosides. The isolate LMM-SA26 carried a ~21 kb conjugative plasmid that harbored the blaKPC-2, blaCTX-M-8, and blaTEM-15 genes. Although carbapenem resistance in the Enterobacteriaceae is still unusual in Venezuela, KPCs have a great potential to spread due to their localization on mobile genetic elements. Therefore, rapid detection of KPC-carrying bacteria with phenotypic and confirmatory molecular tests is essential to establish therapeutic options and effective control measures.